MERGERS AND ACQUISITIONS OF UNIVERSITIES IN RUSSIA AND ABROAD - Alisa V. Melikyan (Высшее образование в России)
The present article describes recent initiatives undertaken by the Russian Government that are aimed at increasing the effectiveness of universities’ operation through their reorganization in the form of a merger or acquisition. The author describes the process of organization of an annual monitoring of Russian universities that is conducted to identify universities and universities’ branches showing signs of inefficiency. The article also provides information about the results of monitoring over the past two years and plans of the Ministry of Education and Science of the Russian Federation of reformation of inefficient universities and universities’ branches.The article dwells on mergers and acquisitions of universities that have occurred in the sector of higher education in Russia over the past few years. The author analyzes typology and geographical location of merged universities. Special attention is paid to the network of federal universities established to develop human capital in the federal districts of Russia. A special example of RANEPA is mentioned as the first Presidential Academy that is formed by the merger of a large number of higher and additional professional education institutions and their branches. The uniqueness of the Academy lies in its extensive territorial structure uniting educational institutions of different levels,located in 53 regions of the country. The article also describes the main objectives behind the leading Russian universities that were formed by merger. The analysis showed that since 2007 there have been over 100 reorganizations of universities in Russia, of which more than 90% supposed that various educational organizations were attached to universities. There were not only horizontal mergers, which suppose that a university is merged with other universities, but also vertical mergers when universities are merged with general, secondary vocational educational institutions. The article describes general trends is state universities’ integration programs of European countries - Denmark, the Netherlands, France, Sweden, and also China. The author analysesstate programs aimed at promoting and supporting university mergers, that where realized in these countries in recent years. The first results of the implementation of these programs and the most interesting practices of universities’ mergers in these countries are described.